2021
DOI: 10.1002/adma.202103394
|View full text |Cite
|
Sign up to set email alerts
|

Passivation of the Buried Interface via Preferential Crystallization of 2D Perovskite on Metal Oxide Transport Layers

Abstract: The open‐circuit voltage (Voc) of perovskite solar cells is limited by non‐radiative recombination at perovskite/carrier transport layer (CTL) interfaces. 2D perovskite post‐treatments offer a means to passivate the top interface; whereas, accessing and passivating the buried interface underneath the perovskite film requires new material synthesis strategies. It is posited that perovskite ink containing species that bind strongly to substrates can spontaneously form a passivating layer with the bottom CTL. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
113
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 121 publications
(121 citation statements)
references
References 65 publications
1
113
0
Order By: Relevance
“…High GUA concentration leads to reduced J sc and FF as a result of the parasitic absorption and the insulating nature of wide bandgap 2D layers. [ 171 ]…”
Section: Perovskite Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…High GUA concentration leads to reduced J sc and FF as a result of the parasitic absorption and the insulating nature of wide bandgap 2D layers. [ 171 ]…”
Section: Perovskite Materialsmentioning
confidence: 99%
“…b) Structural model and corresponding schematics of crystallization process for films with different GUA concentrations on NiO x substrate. Reproduced with permission [171]. Copyright 2021, John Wiley and Sons.…”
mentioning
confidence: 99%
“…However, inorganic hole-transport-layer (HTL) NiO x -based inverted planar PSCs have been troubled by severe open-circuit voltage (V oc ) and fill factor (FF) loss attributed to the charged defects at the film surface, buried interface, and GBs of the perovskite bulk layer. [14][15][16][17] To overcome these defects, achieving a high-quality perovskite film and its defect passivation is critical. Thus, tremendous efforts have been dedicated toward minimizing the perovskite GBs and surface defects by additive and surface engineering.…”
Section: Introductionmentioning
confidence: 99%
“…[13][14][15] Lots of research has been reported on the investigation of the highly crystalline film formation and its post-treatment, to passivate the interface for the improved device performance. [16][17][18][19][20] You and co-workers optimized the PbI 2 content and developed the PEAI top-surface passivation route. [21,22] In contrast, Lu et al doped the A-site of perovskite by incorporating GA þ and reported high-crystalline perovskite films with high efficiency.…”
Section: Introductionmentioning
confidence: 99%